IMPORTANCE OF NATURAL COLORED FOODS IN OUR DAILY DIET - Jagwani, Jyoti (International Journal of Research -GRANTHAALAYAH, 2014)
Colors are not only beautiful to look at. They also affect our well being. By applying the correct color to a specific problem area within our bodies, we can influence our well being. This can also be achieved via the color of our food. The basic rule is: a little bit of everything. If we eat a colorful variety, we will be taking in all the most important nutrients necessary for a smooth functioning of all body functions. This makes one healthy and fit. Our bodies are marvelous. They are designed in a way that they take up the color we are deficient in and excrete those not required. Fruits and vegetables contain hundreds of colorful phytochemicals that act as antioxidant, which help to mop up potentially harmful molecules called free radicals before they get a chance to damage cells.